STUDENTS"™ INSIGHT OF THE DIRECT METHOD IMPLEMENTATION IN IMPROVING THEIR ENGLISH PROFICIENCY - Asri, Anindhiasti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Every student gets the same number of learning chances in the process; however, the results vary from one student to another. Several reasons cause this. The most common are the educational background and environment. This study aimed to understand the students"™ views of the Direct Method implementation in English learning English for Specific Purposes Students (ESP). The research method used is a descriptive qualitative approach, where the sample is taken from Computer Science Students Universitas Duta Bangsa Surakarta. In this study, data collection techniques are through observation and interviews. The observations were done for six meetings through the teaching-learning process. The interviews were done individually. The Direct Method is a traditional method that follows the belief that language is a set of habits. Thus, implementing this method generates various student responses, positively or negatively. However, the students agreed that the method motivates them to do more for their English skills.